'I feel like we finally matter': the role of youth-led approaches in enhancing leisure-induced meaning-making among youth at risk. Issue 4 (2nd October 2019) - Hopper, Tristan D.; Iwasaki, Yoshitaka; Walker, Gordon J.; McHugh, Tara-Leigh F.
ABSTRACT: The purpose of this qualitative case study was to explore how engaging youth at risk through a youth-led approach to recreation and leisure programming can contribute to leisure-induced meaning-making. Seven women (four youth at risk [18–22 years] and three adult recreation practitioners) participated in one-on-one semi-structured interviews. Data were also generated via observation and field notes. A three-phase process of content analysis was used to analyse findings. Findings suggest that youth-led approaches to recreation and leisure programming can contribute to leisure-induced meaning-making by: (a) supporting interests and endeavours; (b) connecting to community; (c) overcoming barriers, together; (d) co-creating safe spaces to be engaged; and (e) developing personal and collective positive outcomes. This research makes theoretical contributions to the leisure literature and provides essential insights regarding proactive engagement of youth at risk and meaning-making for practitioners and policy makers from a practical perspective.